2017
DOI: 10.1002/jia2.25008
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up HIV viral load – lessons from the large‐scale implementation of HIV early infant diagnosis and CD4 testing

Abstract: IntroductionThe scale‐up of effective HIV viral load (VL) testing is an urgent public health priority. Implementation of testing is supported by the availability of accurate, nucleic acid based laboratory and point‐of‐care (POC) VL technologies and strong WHO guidance recommending routine testing to identify treatment failure. However, test implementation faces challenges related to the developing health systems in many low‐resource countries. The purpose of this commentary is to review the challenges and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…While almost all sites reported universal HIV treatment as the standard of care, we found considerable variation in site‐level practices related to rapid ART initiation, with private sector sites and sites in high‐resource settings more likely to report longer times to treatment initiation. Consistent with other research , we also found considerable variation in capacity for viral load monitoring, and almost one‐third of the sites implementing Treat All indicated that they could not routinely request or perform viral load testing. Such gaps were particularly prevalent among sites located in rural areas and in low‐income countries, as well as in countries where Treat All was adopted more recently.…”
Section: Discussionsupporting
confidence: 89%
“…While almost all sites reported universal HIV treatment as the standard of care, we found considerable variation in site‐level practices related to rapid ART initiation, with private sector sites and sites in high‐resource settings more likely to report longer times to treatment initiation. Consistent with other research , we also found considerable variation in capacity for viral load monitoring, and almost one‐third of the sites implementing Treat All indicated that they could not routinely request or perform viral load testing. Such gaps were particularly prevalent among sites located in rural areas and in low‐income countries, as well as in countries where Treat All was adopted more recently.…”
Section: Discussionsupporting
confidence: 89%
“…Monitoring systems with performance indicators should be implemented, ideally with integrated, automated systems that identify patients in need of VL-testing [67]. Creating demand for VL among clinicians and patients will be critical [20,21,35,56,[68][69][70][71]. A recent modelling study predicted that switching patients on efavirenz-based first-line after only one high VL will significantly decrease mortality related to delayed switch [72], POC-VL and same day results would further support this concept.…”
Section: Discussionmentioning
confidence: 99%
“…Peter et al . describe the lessons learned from scale‐up of other laboratory tests, such as EID and CD4+ cell count assays, which can inform scale‐up of viral load testing . Ellman et al .…”
Section: Introductionmentioning
confidence: 99%